PROBLEMATIKA PENERAPAN DIVERSI BAGI ANAK YANG MELAKUKAN TINDAK PIDANA OLEH PENEGAK HUKUM DI ERA GENERASI BETA - Syaiful Bakri; Muhammad Abrori (SAMAWA, 2025)
The purpose of this study, the authors focus on how the implementation ofdiversion for juvenile offenders by law enforcement officials and what arethe obstacles of law enforcement officials in the implementation of diversionfor juvenile offenders, with the aim of analysing the implementation ofdiversion for juvenile offenders by law enforcement officials and analysingwhat are the obstacles of law enforcement officials in the implementation ofdiversion for juvenile offenders. This research method uses a normativelibrary method, namely by reading books related to the title and thisresearch, also supported by the existence of primary and secondary dataobtained from several literatures related to the research. The results of theresearch on the implementation of diversion refer to the regulation of theSupreme Court of the Republic of Indonesia number 4 of 2014 concerningguidelines for the implementation of diversion in the juvenile criminaljustice system and the obstacle is the absence of a clear time in the diversionprocess so that diversion efforts often do not find an agreement.Keywords:Diversion, Law Enforcement, Beta Generation.